TDP‐43 loss of function increases TFEB activity and blocks autophagosome–lysosome fusion. (23rd December 2015) - Xia, Qin; Wang, Hongfeng; Hao, Zongbing; Fu, Cheng; Hu, Qingsong; Gao, Feng; Ren, Haigang; Chen, Dong; Han, Junhai; Ying, Zheng; Wang, Guanghui
Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that is characterized by selective loss of motor neurons in brain and spinal cord. TAR DNA‐binding protein 43 (TDP‐43) was identified as a major component of disease pathogenesis in ALS, frontotemporal lobar degeneration (FTLD), and other neurodegenerative disease. Despite the fact that TDP‐43 is a multi‐functional protein involved in RNA processing and a large number of TDP‐43 RNA targets have been discovered, the initial toxic effect and the pathogenic mechanism underlying TDP‐43‐linked neurodegeneration remain elusive. In this study, we found that loss of TDP‐43 strongly induced a nuclear translocation of TFEB, the master regulator of lysosomal biogenesis and autophagy, through targeting the mTORC1 key component raptor. This regulation in turn enhanced global gene expressions in the autophagy–lysosome pathway (ALP) and increased autophagosomal and lysosomal biogenesis. However, loss of TDP‐43 also impaired the fusion of autophagosomes with lysosomes through dynactin 1 downregulation, leading to accumulation of immature autophagic vesicles and overwhelmed ALP function. Importantly, inhibition of mTORC1 signaling by rapamycin treatment aggravated the neurodegenerative phenotype in a TDP‐43‐depleted Drosophila model, whereas activation of mTORC1 signaling by PA treatment ameliorated the neurodegenerative phenotype. Taken together, our data indicate that impaired mTORC1 signaling and influenced ALP may contribute to TDP‐43‐mediated neurodegeneration. Synopsis: RNA binding protein TDP‐43 aggregates are linked to ALS. TDP‐43 deficiency leads to decreased dynactin 1 expression, blocking autophagic flux; it also reduces mTORC1 activity, leading to increased autophagy and lysosome gene expression via TFEB. Abnormal regulation of autophagy contributes to TDP‐43‐associated neurotoxicity. TDP‐43 is required for raptor mRNA stability and thus for mTORC1 activity. Loss of TDP‐43 results in TFEB nuclear translocation and in increased autophagosomal and lysosomal biogenesis. Loss of TDP‐43 leads to impaired autophagosome–lysosome fusion due to reduced dynactin 1 levels. The neurotoxicity of TDP‐43 loss of function can be rescued by activation of mTORC1 signaling in Drosophila . Abstract : RNA binding protein TDP‐43 aggregates are linked to ALS. TDP‐43 deficiency leads to decreased dynactin 1 expression, blocking autophagic flux; it also reduces mTORC1 activity, leading to increased autophagy and lysosome gene expression via TFEB. Abnormal regulation of autophagy contributes to TDP‐43‐associated neurotoxicity.